Research on the optimal design and process parameters of a castor seed cleaning machine - Aliiev, Elchyn; Алієв, Ельчин Бахтияр огли; Holovchenko, Valentin; Головченко, Валентин Володимирович; Aliieva, Olha; Алієва, Ольга Юріївна (Czech Academy of Agricultural Sciences, 2026)
In the context of the modern EU bioeconomy, the use of industrial crops, particularly castor beans (Ricinus communis L.), is relevant for the production of industrial and energy products without competing with food crops. Castor oil is used for the production of biodiesel, lubricants, paints and coatings, cosmetics, and pharmaceuticals. In Ukraine, castor beans can be cultivated on low-yield soils, with seed yields ranging from 1.5 t/ha to 2.1 t/ha depending on the variety. However, the morphological features of the fruits and uneven ripening complicate the mechanisation of harvesting and seed cleaning processes. Existing equipment designed for other crops cannot be applied due to the risk of damaging the castor seeds. A design of a castor seed cleaning machine has been proposed, combining mechanical fruit shelling with the aerodynamic separation of the mixture. The machine is equipped with an eccentric crushing cone, rubber linings, a pneumatic separation channel, a cyclone, and an automated control unit. As a result of numerical modelling and experimental studies of the process of separating and cleaning castor seeds, dependencies were obtained for the productivity of the developed machine Q, power consumption P, specific energy consumption E, fraction of unshelled fruits (segments) ξf, content of the clean seed in the seed collector ψs-s depending on the distance between the reverse and crushing cones δ, rotation frequency of the crushing cone n, diameter of the feed opening Din, inclination angle of the crushing cone axis γ, and airflow velocity V. A multi-criteria optimisation method was applied to find the optimal operating modes: δ = 10.8 mm; n = 282 rpm; V = 3.6 m/s; Din = 98 mm; γ = 3.6°; β = 20.3°. The following results were achieved: E = 0.0394 MJ/kg; Q = 163.4 kg/h; P = 1 861 W; ξf = 0.099; ψs-s = 0.958. The obtained results confirm the efficiency of the proposed design for industrial implementation. У контексті сучасної біоекономіки ЄС використання технічних культур, зокрема рицини (Ricinus communis L.), є актуальним для виробництва промислової та енергетичної продукції без конкуренції з продовольчими культурами. Рицинова олія застосовується для виробництва біодизеля, мастильних матеріалів, фарб і покриттів, косметики та фармацевтичних засобів. В Україні рицину можна вирощувати на малопродуктивних ґрунтах із врожайністю насіння від 1,5 до 2,1 т/га залежно від сорту. Однак морфологічні особливості плодів і нерівномірне достигання ускладнюють механізацію процесів збирання та очищення насіння. Існуюче обладнання, призначене для інших культур, не може бути використане через ризик пошкодження насіння рицини. Запропоновано конструкцію машини для очищення насіння рицини, що поєднує механічне лущення плодів з аеродинамічною сепарацією суміші. Машина оснащена ексцентриковим дробильним конусом, гумовими накладками, пневматичним сепараційним каналом, циклоном та автоматизованим блоком керування. У результаті чисельного моделювання та експериментальних досліджень процесу розділення й очищення насіння рицини отримано залежності для продуктивності розробленої машини Q, споживаної потужності P, питомих енерговитрат E, частки нелущених плодів (сегментів) ξf, вмісту чистого насіння у насіннєзбірнику ψs-s залежно від відстані між відбійним і дробильним конусами δ, частоти обертання дробильного конуса n, діаметра завантажувального отвору Din, кута нахилу осі дробильного конуса γ та швидкості повітряного потоку V. Застосовано метод багатокритеріальної оптимізації для визначення оптимальних режимів роботи: δ = 10,8 мм; n = 282 об/хв; V = 3,6 м/с; Din = 98 мм; γ = 3,6°; β = 20,3°. Отримано такі результати: E = 0,0394 МДж/кг; Q = 163,4 кг/год; P = 1861 Вт; ξf = 0,099; ψs-s = 0,958. Отримані результати підтверджують ефективність запропонованої конструкції для промислового впровадження.
Дослідження оптимального конструктивного виконання та параметрів машини для очищення насіння рицини
Keywords: experiment; експеримент; mechanical shelling; механічне лущення; numerical simulation; чисельне моделювання; productivity; продуктивність; quality; якість; regression models; регресійні моделі; specific energy; питома енергія